The Role Of The New Criminal Code As An Effort To Eradicate Criminal Acts Of Terrorism In Indonesia - Milda Istiqomah; Rika Kurniaty; Rizky Kurnia (CV. AFDIFAL MAJU BERKAH, 2024)
Terrorism is a serious threat faced by countries and nations, including Indonesia. Terrorism is considered a crime against humanity, an international crime that endangers world security and peace, and harms the welfare of society. One of the efforts to overcome the threat of terrorism is through the implementation of the new Criminal Code (KUHP) which was formalized through Law Number 1 Year 2023. This new Criminal Code replaces the old Criminal Code that has been in effect since the Dutch East Indies colonial period. This study aims to analyze the role of the new Criminal Code in efforts to eradicate criminal acts of terrorism in Indonesia. The research method used is legal research with a normative juridical approach, with data collection techniques through literature studies. Data analysis is conducted qualitatively, involving the stages of data reduction, data presentation, and conclusion drawing. The result shows that the new Criminal Code has an important role in the effort to eradicate terrorism in Indonesia. The replacement of the old Criminal Code with the new one includes a more comprehensive regulation of the crime of terrorism and in accordance with the demands of modern times, such as providing clearer and more complete definitions, more severe criminal penalties, and firmer and clearer provisions on the prevention of criminal acts. Therefore, the New Criminal Code can be an effective instrument in the effort to eradicate terrorism in Indonesia